Aktualisasi Dan Signifikansi Buku Ajar Pembelajaran Bahasa Arab Untuk Anak-Anak Di Lkp Ibnu Khaldun Driyorejo Gresik - Al-Ayyubi, Sholihudin (FATAWA: Jurnal Pendidikan Agama Islam, 2021)
In Arabic language learning, textbooks strongly support the achievement of the ability of learners. In LKP Ibnu Khaldun, there is a teaching book as a teacher and student handbook containing materials, Arabic games, songs and expressions in Arabic. This research includes literature research with qualitative approach, trying to analyze the actualization and significance of textbooks in the process of learning Arabic in intensive classes of Arabic LKP Ibn Khaldun. Data collection method with documentation and content analysis descriptively qualitatively. The book, published in 2020 and already isbn, has been applied to Arabic language learning in LKP Ibnu Khaldun covering 26 themes. For mufradat learning for beginners, especially children, this book has many advantages, namely: a. In terms of content, there are many Arabic-themed vocabularies, games, songs and expressions in Arabic, b. In terms of presentation, each theme is equipped with illustrations of colored objects. The significance of this textbook is: a. Multiplying the memorization of new vocabulary 200-400 words, b. Increase interest in learning the contents of books with illustrations of colored objects with the mention of Arabic vocabulary, c. Multiply memorization of Arabic songs translated from Indonesian children's songs, d. Accustomed to the practice of speaking through the practice of expression in Arabic, e. Learning Arabic is more interesting because of the practice of memorizing vocabulary games.